Supramolecular Covalence in Bifurcated Chalcogen Bonding - Bora, Pankaj Lochan; Novák, Martin; Novotný, Jan; Foroutan-Nejad, Cina; Marek, Radek (Chemistry (Weinheim an der Bergstrasse, Germany), 2017)
Supramolecular interactions are generally classified as noncovalent. However, recent studies have demonstrated that many of these interactions are stabilized by a significant covalent component. Herein, for systems of the general structure [MX6 ]2- :YX2 (M=Se or Pt; Y=S, Se, or Te; X=F, Cl, Br, I), featuring bifurcated chalcogen bonding, it is shown that, although electrostatic parameters are useful for estimating the long-range electrostatic component of the interaction, they fail to predict the correct order of binding energies in a series of compounds. Instead, the Lewis basicity of the individual substituents X on the chalcogen atom governs the trends in the binding energies through fine-tuning the covalent character of the chalcogen bond. The effects of substituents on the binding energy and supramolecular electron sharing are consistently identified by an arsenal of theoretical methods, ranging from approaches based on the quantum chemical topology to analytical tools based on the localized molecular orbitals. The chalcogen bonding investigated herein is driven by orbital interactions with significant electron sharing; this can be designated as supramolecular covalence.
Keywords: halogen bonding; supramolecular chemistry; chalcogens; computational chemistry; charge transfer